The NEW INTELLIGENT TECHNOLOGIES- THE PROBLEMS AND OPPORTUNITIES - Dr. Rusi Marinov, (IJRDO - Journal of Social Science and Humanities Research, 2019)
In this paper, attention is focused on threats to people and security, which may be caused by the intelligent technologies of recent years, such as neural networks, deep learning, and artificial intelligence. In nowadays, mobile companies, social networks, various computer applications, smart devices constantly collect data for people without they know it and they are used to develop intelligent software systems to predict future behavior. One of the ways to protect citizens is to change the approach to the use of technology. At present, people do not understand the dark side of the platforms until they are involved in activities leading to personal and financial losses.